THE INFLUENCE OF COMPETENCE, INDEPENDENCE AND ETHICS ON THE PERFORMANCE OF GOVERNMENT INTERNAL CONTROL APPARATUS (APIP) INSPECTORATE TOJO UNA-UNA REGENCY - Silfianti, Silfianti; Hasanuddin, Bakri; Mahardiana, Lina (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
The aim and objective of this research is to determine simultaneously and partially how competence, independence, and ethics influence the performance of the Government Internal Audit Apparatus (APIP) of the Regional Inspectorate of Tojo Una-Una Regency. The research population was 32 respondents, using proportional techniques. The data analysis tool used in this research is multiple linear regression. The research results prove that simultaneously competency, independence, and ethics have a significant effect on the performance of the Government Internal Audit Apparatus (APIP) of the Regional Inspectorate of Tojo Una-una Regency, while the results of the partial test prove that competency, independence, and ethics have a significant effect on the performance of the Government Internal Oversight Apparatus ( APIP) Tojo Una-una Regency Regional Inspectorate.